Technological progress, occupational structure and gender gaps in the German labour market - Ronald Bachmann; Myrielle Gonschor (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
We analyze if technological progress and the corresponding change in the occupational structure have improved the relative position of women in the labour market. We show that the share of women rises most strongly in non-routine cognitive and manual occupations, but declines in routine occupations. While the share of women also rises relatively strongly in high-paying occupations, womens' individual-level wages lag behind which implies withinoccupation gender wage gaps. A decomposition exercise shows that composition effects with respect to both individual and job characteristics can explain the rise of female shares in the top tier of the labour market to an extent. However, the unexplained part of the decomposition is sizeable, indicating that developments such as technological progress are relevant. – – Wir untersuchen, ob sich durch den technologischen Fortschritt und die entsprechende Veränderung der Berufsstruktur die relative Stellung der Frauen auf dem Arbeitsmarkt verbessert hat. Wir zeigen, dass der Frauenanteil am stärksten in nicht-routine kognitiven und manuellen Berufen angestiegen, in Routineberufen jedoch gesunken ist. Während der Frauenanteil auch in Hochlohnberufen stark gestiegen ist, entwickelten sich die individuellen Löhne der Frauen weniger stark, woraus sich eine geschlechtsspezifische Lohnlücke innerhalb von Berufen ergibt. Die Dekompositionsanalyse zeigt, dass Kompositionseffekte in Bezug auf individuelle und berufliche Merkmale den Anstieg des Frauenanteils im höheren Lohnbereich bis zu einem gewissen Grad erklären können. Der unerklärte Teil der Dekomposition deutet zudem darauf hin, dass Entwicklungen wie der technische Fortschritt eine wichtige Rolle spielen.
Keywords: J21; J31; O33; 330; Female labour market participation; occupations; tasks; technological progress